Vitamin D levels in children and adolescents with obsessive compulsive disorder - Yazici, Kemal Utku; Yazici, Ipek Percinel; Ustundag, Bilal (Taylor & Francis Ltd, 2018)
Background: Recent studies showed that vitamin D deficiency may lead to dysfunctional changes in the brain and may be associated with neuropsychiatric diseases.Aims: The present study aims to investigate vitamin D, calcium, phosphorus and alkaline phosphatase levels in children and adolescents diagnosed with obsessive-compulsive disorder (OCD) and compared them to healthy controls. Additionally, the correlation of OCD symptom severity with serum vitamin D level will be analyzed.Methods: A semi-structured interview form (K-SADS-PL) was used to diagnose OCD and other comorbidities in accordance with DSM-IV criteria. In addition, all participants were assessed with clinical interviews based on DSM-5 OCD diagnostic criteria. Children's Yale Brown Obsession Compulsion Scale (CY-BOCS) and Children's Depression Inventory were used in the clinical evaluation.Results: Vitamin D levels were lower in patients diagnosed with OCD (15.886.96ng/mL) when compared to healthy controls (18.21 +/- 13.24ng/mL), but the difference was not statistically significant (p=.234). Serum calcium, serum phosphate and serum alkaline phosphatase levels were not different between the groups. A negative correlation was found between serum 25OH-D3 levels and obsession scale scores in CY-BOCS.Conclusions: To our knowledge this is the first study that evaluated vitamin D levels in OCD patients without comorbidity. The vitamin D levels of newly diagnosed OCD cases were lower but not statistically different than healthy controls. Furthermore, the study does also not support the presence of a significant association between serum vitamin D levels and OCD.
Keywords: Adolescent; children; obsessive compulsive disorder; vitamin D